LncRNA FAM13A-AS1 Regulates Proliferation and Apoptosis of Cervical Cancer Cells by Targeting miRNA-205-3p/DDI2 Axis. (23rd June 2022) - Qiu, Zhiqin; He, Lin; Yu, Feng; Lv, Hui; Zhou, Ye
Abstract : The aim of this study was to explore the function of long noncoding RNA (lncRNA) FAM13A-AS1 and its associated mechanism in cervical cancer. A total of 30 cervical cancer tissues and adjacent tissues were collected. Cervical cancer cell lines, including SiHa and HeLa, were transfected with constructs expressing LV-FAM13A-AS1, silencing RNA LV-siFAM13A-AS1, miRNA mimics, and miRNA inhibitors. RT-qPCR was used to detect the expression of FAM13A-AS1 in cervical cancer tissues, including SiHa, HeLa, and HUCEC cells. MTT, flow cytometry, and transwell assays were performed to explore the influence of FAM13A-AS1 on cervical cancer cell proliferation, apoptosis, invasion, and migration. A bioinformatics analysis and a dual-luciferase assay were carried to confirm the target relationship between FAM13A-AS1 or DDI2 and miRNA-205-3p. Finally, in vivo tumorigenesis experiments were performed in nude mice to explore the effect of FAM13A-AS1 expression on cervical cancer. Low FAM13A-AS1 expression and high miRNA-205-3p expression were observed in cervical cancer tissues and cell lines (SiHa and HeLa). Upregulating the expression of FAM13A-AS1 inhibited proliferation, migration, and invasion of SiHa and HeLa cells, while the apoptosis of SiHa and HeLa cells was increased. More importantly, LV-FAM13A-AS1 could improve tumor development in vivo. In addition, FAM13A-AS1 negatively regulated the expression of miRNA-205-3p, while miRNA-205-3p reduced DDI2 expression, and miRNA-205-3p mimic reversed the effects of FAM13A-AS1 overexpression in vitro. In conclusion, FAM13A-AS1 inhibits the progression of cervical cancer by targeting the miRNA-205-3p/DDI2 axis, suggesting that FAM13A-AS1 might be a potential target for cancer cell treatment.